Diagnostic Challenge Of Hematolymphoid Neoplasm Mimicking Advanced Breast Cancer In A Young Woman: A Case Report - Yuliansyah, Lalu Fauzan Adi; Lissanawidya, Putri; Susilo, Hery; Zulhadi, Lalu Fatria (LITPAM, 2026)
Hematolymphoid neoplasms involving the breast are extremely rare and may closely mimic advanced breast carcinoma in both clinical presentation and radiological findings. This overlap poses a significant diagnostic challenge, particularly in young patients, and may lead to misdiagnosis and inappropriate management. We report the case of a 29-year-old woman who presented with a right breast mass, progressive back pain, paraparesis, and extranodal involvement including a palatal mass and extensive skeletal lesions. Initial clinical evaluation, elevated CA 15-3 levels, and imaging findings suggested advanced breast carcinoma with widespread metastases. Radiological assessment using ultrasonography and magnetic resonance imaging demonstrated a suspicious breast mass (BIRADS 4B), diffuse bone marrow infiltration, skull base involvement, and multiple lymphadenopathies. Fine-needle aspiration biopsy (FNAB) of the breast, palate, and cervical lymph nodes revealed features of a malignant round cell tumor consistent with a hematolymphoid neoplasm. Immunohistochemical analysis showed negative cytokeratin expression and diffuse CD4 positivity, supporting a lymphoid origin and excluding epithelial breast carcinoma. These findings shifted the diagnosis from metastatic breast cancer to a systemic hematolymphoid malignancy. Hematolymphoid neoplasms should be considered in the differential diagnosis of young patients presenting with breast masses and extensive systemic involvement. Histopathological confirmation supported by immunohistochemistry is essential to establish an accurate diagnosis and guide appropriate therapy. Early recognition is crucial, as prognosis and treatment strategies for lymphoma differ substantially from those of advanced breast carcinoma.